PEMBERDAYAAN KEMANDIRIAN IBU DALAM MANAJEMEN PEMBERIAN ASI DAN MPASI MELALUI PENYULUHAN KESEHATAN DI BANJAR KESIMPAR KAWAN DESA KESIMPAR KECAMATAN ABANG, KABUPATEN KARANGASEM - Ni Ketut Citrawati; Ni Ketut Ayu Mirayanti; Ni Komang Sukra Andini; Sang Ayu Ketut Candrawati; Putu Gede Subhaktiyasa (Politeknik Negeri Sriwijaya, 2023)
Breastfeeding babies until six months without any other food is very beneficial because it can protect babies from various diseases that can cause death. Exclusive breastfeeding can prevent postpartum hemorrhage, stop excessive bleeding during menstruation, lose weight quickly, and prevent cancer risk. Babies are given complete breastfeeding weight if the average is more excellent than those given other food from the start. This happens because the other food provided does not contain zinc and iron, suitable for baby growth. The activity was carried out at the Kesimpar Kawan Kesimpar Village hamlet, Abang District, Karangasem Regency. This Community Service activity is an outreach about exclusive breastfeeding and complementary feeding. The targets used in this community service activity were 50 pregnant women and nursing mothers. The implementation of community service activities consisted of a pretest on the knowledge of pregnant and breastfeeding women about exclusive breastfeeding and complementary foods, then continued with the provision of health information using the lecture and demonstration method. After that, the activity continued with a posttest.